KEANEKARAGAMAN JENIS DAN KARAKTERISTIK HABITAT ULAR (Serpentes) DI KAWASAN HUTAN SEKUNDER - Rafli Alviansyah; Toto Supartono; Nurdin Nurdin (Journal of Forestry And Environment, 2022)
The type of snake (Sepentes) has not been properly, completely and thoroughly recorded further research on species diversity and habitat characteristics of snakes (Serpentes) in the forest secondary nature in Tundagan Village, as well as as an initial published data collection with more complete as desired and sustainable for the sub-order Serpentes. The purpose of this research are 1) Knowing the level of diversity of snake species (Serpentes) in the Tundagan secondary forest. 2) Knowing the habitat characteristics of snakes (Serpentes) based on vegetation and environmental factors. found as many as 2 families and 12 species of snakes (Serpentes). In the habitus of undergrowth dominated by Begonia (Begonia sp.) by 22.85%, In the bush habitus it is known that The highest important value index was obtained by the Senggani species (Melastoma sp.) which was 75.51%, the highest important value index on tree habitus was obtained from the Bunut species (Ficus glauca) which is 63.91%. The number of snake species (Serpentes) is most commonly found when the temperature is daily averages at 23°C and 24.5°C which is 6 species. The highest number of species was found when The average daily humidity is 86%, which is found as many as 6 species.Belum terdatanya jenis ular (Sepentes) dengan baik, lengkap dan menyeluruh sehingga diperlukan penelitian lebih lanjut mengenai keanekaragaman jenis dan karakteristik habitat ular (Serpentes) di hutan alam sekunder di Desa Tundagan, serta sebagai pendataan awal yang terpublikasikan dengan lebih lengkap sebagai acuan dan dapat berkelanjutan bagi sub ordo Serpentes. Tujuan dalam penelitian ini adalah 1) Mengetahui tingkat keanekaragaman jenis ular (Serpentes) di hutan sekunder Tundagan. 2) Mengetahui karakteristik habitat ular (Serpentes) berdasarkan vegetasi dan faktor-faktor lingkungan. ditemukan sebanyak 2 famili yakni dan 12 spesies ular (Serpentes), Pada habitus tumbuhan bawah didominasi oleh Begonia (Begonia sp.) sebesar 22.85%, Pada habitus semak diketahui bahwa indeks nilai penting tertinggi diperoleh oleh spesies Senggani (Melastoma sp.) yakni sebesar 75.51%, Indeks nilai penting tertinggi pada habitus pohon diperoleh oleh jenis Bunut (Ficus glauca) yakni sebesar 63.91%, Jumlah jenis ular (Serpentes) paling banyak ditemukan ketika suhu rata-rata harian pada 23°C dan 24,5°C yakni 6 jenis, Jumlah jenis tertinggi ditemukan ketika kelembaban rata-rata harian 86% yakni ditemukan sebanyak 6 jenis